Penerapan Model Problem Based Learning Berbantuan Media Interaktif Untuk Meningkatkan Hasil Belajar Matematika Siswa - Septiani Ari Pertiwi, Ni Luh; Dibia, I Ketut (Journal of Education Action Research, 2018)
This research was a classroom action research that aimed at improving the learning outcomes of Mathematics through the application of Problem-Based Learning assisted by Interactive Media. Each cycle consists of planning, execution, observation or evaluation, and reflection. The subjects of this study were the eighth grade students of Elementary School of Undiksha Laboratory which consisting of 24 male students and 10 female students. The form of data analysis used is quantitative descriptive data analysis. The data of the research results showed that, based on the first cycle analysis, the quantity of students who got a minimum score of 80 were 26 students or 76.47%, so there were still 8 students left who got score below than 80. While on the second cycle the quantity of students who got a minimum score of 80 were 30 students or reach 88,23% and there were only 4 students who did not get the value 80. Then, the results of the first cycle analysis about the percentage of knowledge learning achievement of Mathematics reached 82.75% which was categorized as high. While in the second cycle reached 90.1% which based on the category of learning outcomes Mathematics knowledge was categorized as very high. The results of this study indicated that the implementation of Problem-Based Learning assisted by Interactive Media could improve the learning outcomes of Mathematics students in eighth grade students of Elementary School of Undiksha Laboratory Year 2017/2018.